The Use of Story Completion Method in Career Counselling - Amundson, Norman E. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper explores how a story completion method can be used in career counselling to help clients identify and clarify their values and problem solving strategies. A series of situations are presented for use with youth and adults. In using the approach there is an emphasis on flexibility and collaboration within a structured interviewing format.